Presenting the model of Olympic education in Iranian schools - Maziar Meghdadi; MohammadReza Esmaeili; Farzad Ghafouri (International Journal of Psychosocial Rehabilitation, 2020)
Olympic education is the philosophical-educational theory of the Olympics that is used to learn the concepts of physical, social, moral and human values in sports activities (1,2). Olympic is a general concept that does not focuses only on the development of physical strength, but seeks healthier people with a happier outlook and a more peaceful view of the world (3). The Olympics recognize and appreciate the efforts of individuals and do not accept any discrimination between nations, races, political systems, etc. (4). Olympic educational values are learned through practice, which ultimately changes the behavior of individuals and their perception of society (5).